Doctors Without Borders: Coherent Principles - Deus, S.; Reis,R. (Sur - International Journal on Human Rights, 2017)
This text explains the reasons, including the internal debate, for Doctors without Borders’ recent decision to suspend funds received from the European Union for the development of its humanitarian work, doing justice to the values that guide the organisation: Independence, medical ethics, neutrality and impartiality. The refusal to continue receiving economic assistance is a critical position in the face of recent migratory policies adopted by the European Union, signalling the negative impact that these policies are having on thousands of vulnerable people, who are, after all, the principal focus of MSF’s humanitarian work